Peran Media “Alphabet Magnetic “ Dalam Pembelajaran Membaca: Studi di SD Kelas Tinggi - Siti Hamidah (JURNAL EDUKASI: KAJIAN ILMU PENDIDIKAN, 2024)
This research aims to describe the role of magnetic alphabet media when learning to read in high school elementary school students. The "Magnetic Alphabet" media is a learning aid that uses magnetic letters to help students recognize and form words. This research was conducted at the Kalipecabean village hall by taking students from Kalipecabean Elementary School consisting of 6 people with details of 1 female student and 5 male students as research subjects. The research method used was qualitative involving interviews with school principals and teachers regarding students. who cannot read, observe and document directly during the learning process. The VAKT method focuses on the use of various multisensory aspects in humans, so it is hoped that it will be able to provide solutions to teachers in teaching students who have difficulty learning to read. The research results show that the use of the "Magnetic Alphabet" significantly improves students' reading abilities as evidenced by the results of the analysis of the percentage of research subjects showing high figures, 97.5% RK, 87.5% RF, 95% FN, 90%, FA, 97, 5% AN, and 92.5% OC. Thus, the "Magnetic Alphabet" media has proven to be effective as an aid in learning to read in upper elementary grades, and is recommended for widespread use in efforts to increase student literacy at the elementary education level.